Low-temperature binding of NO adsorbed on MIL-100(Al)-A case study for the application of high resolution pulsed EPR methods and DFT calculations - Mendt, Matthias; Barth, Benjamin; Hartmann, Martin; Poeppl, Andreas (Journal of Chemical Physics, 2017)
The low-temperature binding of nitric oxide (NO) in the metal-organic framework MIL-100(Al) has been investigated by pulsed electron nuclear double resonance and hyperfine sublevel correlation spectroscopy. Three NO adsorption species have been identified. Among them, one species has been verified experimentally to bind directly to an Al-27 atom and all its relevant N-14 and Al-27 hyperfine interaction parameters have been determined spectroscopically. Those parameters fit well to the calculated ones of a theoretical cluster model, which was derived by density functional theory (DFT) in the present work and describes the low temperature binding of NO to the regular coordinatively unsaturated Al3+ site of the MIL-100(Al) structure. As a result, the Lewis acidity of that site has been characterized using the NO molecule as an electron paramagnetic resonance active probe. The DFT derived wave function analysis revealed a bent end-on coordination of the NO molecule adsorbed at that site which is almost purely ionic and has a weak binding energy. The calculated flat potential energy surface of this species indicates the ability of the NO molecule to freely rotate at intermediate temperatures while it is still binding to the Al3+ site. For the other two NO adsorption species, no structural models could be derived, but one of them is indicated to be adsorbed at the organic part of the metal-organic framework. Hyperfine interactions with protons, weakly coupled to the observed NO adsorption species, have also been measured by pulsed electron paramagnetic resonance and found to be consistent with their attribution to protons of the MIL-100(Al) benzenetricarboxylate ligand molecules. Published by AIP Publishing.